(untitled) (Eurasian Scientific Herald, 2022)
The paper considers the reaction of a cylindrical layer located in a viscoelastic medium, when exposed to a transverse (longitudinal) seismic wave. It has been established that the maximum dynamic stress is 10-15% higher than the static one, and the wave numbers at which the maximum value is reached